Walnut intake may increase circulating adiponectin and leptin levels but does not improve glycemic biomarkers: A systematic review and meta-analysis of randomized clinical trials - Yang, Ling; Guo, Zhiyang; Qi, Shuwen; Fang, Tao; Zhu, Hongyan; Santos, Heitor O.; Khani, Vahid; Wong, Chun Hoong; Qiu, Zhiyun (Complementary therapies in medicine, 2020)
•The walnut administration significant increasing serum leptin and adiponectin.•The walnut administration did not changes in fasting blood glucose (FBG).•The walnut administration did not changes in insulin, and glycated hemoglobin (HbA1c) concentrations. Background & objective: Walnut intake is considered a healthy dietary approach worldwide, particularly as a nutritional tool for the management of obesity and cardiometabolic disorders. Among these lines, leptin and adiponectin, as well as glycemic biomarkers, deserve further attention. We aimed to examine the impact of walnut intake on circulation levels of leptin and adiponectin through a systematic review and meta-analysis of randomized clinical trials (RCTs); secondarily, assessing the glycemic profile as well. The literature search was implemented in four following databases: Web of Science, Scopus, PubMed/Medline, and Google Scholar, thus, determining studies that measured the effects of walnut consumption on adiponectin, leptin, and glycemic biomarkers levels from 2004 up to December 2019. Fourteen trials were include in the meta-analysis, with an intervention period ranging from 5 weeks to 12 months.Walnut intake increased leptin (weighted mean difference (WMD): 2.502 ng/mL; 95 % CI: 2.147–2.856, p < 0.001) and adiponectin (WMD: 0.440 ng/mL; 95 % CI: 0.323 to 0.557, p < 0.001) levels. Pertaining to glycemic biomarkers, neither overall analyses nor sub-analyses corroborated with changes in fasting blood glucose (WMD: 0.500 mg/dL, 95 % CI: -0.596, 1.596, p = 0.371), insulin (WMD: -0.21 mg/dL, 95 % CI: -0.67, 0.24, p = 0.367), and glycated hemoglobin (WMD: 0.004 mg/dL, 95 % CI: -0.041, 0.049, p = 0.870) concentrations. Walnut intake may increase leptin and adiponectin levels but does not improve glycemic biomarkers.